Higher Education : Social Reconstruction of 21st Century - Sangita Pati,; Dr .sasadhar Dash, (IJRDO- Journal of Educational Research, 2020)
Now the era of 21st Century, changing is occurred due to new phenomena and new ideologies. Information Communication Technology have change the entire social, political and economical frame work most of the countries of the world. Social reformation, Social reconstructive and national reconstruction depends upon the higher level of education. So higher education in India stands as an immobile colossus – insensitive to the changing contents of Cotemporary life; unresponsive to the challenges of today and tomorrow, and absorbed So completely in trying to preserve its structural from that, it does not have the time to consider its own larger purpose. Its maladies have been investigated by an unending       chain of committees, working groups, task forces and commissions. So that higher education plays an important role not only construction but also shaping society as per the need of the hour.